Polymer optical waveguide based on integrated optics - SHARMA, S; MISRA, S; TRIPATHI, K (2003)
The fabrication and characterization of refractive index profiles of multimode mode polymer optical waveguides is reported. Effect of annealing temperature on guided losses of polymer (polystyrene) thin film optical waveguide is also presented. Efficient coupling over a 110 nm spectral bandwidth was experimentally demonstrated with a prism-coupler designed to match the dispersion of a particular waveguide.